2020
DOI: 10.1038/s41598-020-65588-8
|View full text |Cite
|
Sign up to set email alerts
|

Allelic sequence variation in the Sub1A, Sub1B and Sub1C genes among diverse rice cultivars and its association with submergence tolerance

Abstract: Erratic rainfall leading to flash flooding causes huge yield losses in lowland rice. The traditional varieties and landraces of rice possess variable levels of tolerance to submergence stress, but gene discovery and utilization of these resources has been limited to the Sub1A-1 allele from variety FR13A. Therefore, we analysed the allelic sequence variation in three Sub1 genes in a panel of 179 rice genotypes and its association with submergence tolerance. Population structure and diversity analysis based on a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 47 publications
1
23
0
Order By: Relevance
“…The circum-aus accessions respond differently to variation in water availability: Bhadoia 303 shows excellent flooding tolerance as an accession with the SNORKEL1 and -2 haplotypes (Dwivedi et al, 1992;Hattori et al, 2009). Kasalath has the "reference" SUB1A, -B, and -C haplotypes of the submergence-tolerant accession FR13A, and these alleles alter patterns of submergence and drought tolerance (Xu et al, 2006;Fukao et al, 2011;Singh et al, 2020).…”
Section: Baseline and Drought-induced Transcript Expression Show Gene...mentioning
confidence: 99%
“…The circum-aus accessions respond differently to variation in water availability: Bhadoia 303 shows excellent flooding tolerance as an accession with the SNORKEL1 and -2 haplotypes (Dwivedi et al, 1992;Hattori et al, 2009). Kasalath has the "reference" SUB1A, -B, and -C haplotypes of the submergence-tolerant accession FR13A, and these alleles alter patterns of submergence and drought tolerance (Xu et al, 2006;Fukao et al, 2011;Singh et al, 2020).…”
Section: Baseline and Drought-induced Transcript Expression Show Gene...mentioning
confidence: 99%
“…The circum -aus accessions respond differently to variation in water availability: Bhadoia 303 shows excellent flooding tolerance as an accession with the SNORKEL1 and -2 haplotypes (Dwivedi et al, 1992; Hattori et al, 2009). Kasalath has the “reference” SUB1A , - B , and – C haplotypes of the submergence-tolerant accession FR13A, and these alleles alter patterns of submergence and drought tolerance (Fukao et al, 2011; Singh et al, 2020; Xu et al, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…Pangenomes for many crops including maize and rice are already available in public repositories and have been used to uncover novel sequences for traits of interest and structural variations (>50 bp) in genomic regions regulating these traits. For example, in rice, analysis of genome assemblies for multiple genotypes available at the RicePanGenome database (http://db.ncgr.ac.cn/ RicePanGenome/) were recently used to analyze allelic variations of Sub1 genes (Singh et al, 2020). In addition, authors there identified sources of flood tolerance in 18 cultivars that were not associated with Sub1 genes, which could be used to develop superior lines for flood resistance (Singh et al, 2020).…”
Section: Discussionmentioning
confidence: 99%